Atividade eletromiográfica de músculos do core e reto femoral no exercício abdominal tradicional e com equipamento Ab Max Genis® - Naves Junior, José Duarte (2024)
Commercial abdominal exercise equipment is designed to provide adequate support and resistance during abdominal muscle strengthening movements. Some studies have shown positive results regarding abdominal muscle strengthening with the use of these equipments. This study aimed to evaluate and compare the electromyographic activity of the Upper Abdominal Rectus (UAR) and Lower Abdominal Rectus (LAR), External Oblique Abdominus (EOA), and Rectus Femoris (RF) muscles during traditional abdominal exercise (TE) and exercise using the Ab Max Genis® equipment. A convenience sample composed of 15 physically active male volunteers, with a mean age of 22 ± 3.36 years, body mass of 69.79 ± 10.72 kg, height of 177.80 ± 8.46 cm, body fat percentage of 12.01 ± 3.79%, and with a minimum of one year of resistance training practice, participated in the study. Electromyographic data were collected during five repetitions of each abdominal exercise (TE and Ab Max Genis® at levels AB1, AB2, AB3, and AB4). Simple differential surface electrodes were used to capture the electromyographic signal, a computerized electromyograph (EMG System do Brasil EMG800RF) was used, and the obtained signal was quantified by the root mean square (RMS) and normalized (RMSn) by the maximum voluntary isometric contraction (MVIC). The normality test and sphericity test were conducted; if sphericity were not confirmed, the Greenhouse-Geisser adjustment would be applied. One-way repeated measures analysis of variance (ANOVA) was used to compare the mean normalized RMS (RMSn) values of the same muscle in different exercises; in all analyses, the Bonferroni multiple comparisons test was performed to identify any differences. The results demonstrate that EMG activity in the Ab Max Genis® equipment was lower in the UAR muscle, similar in the LAR muscle, and higher in the EOA muscle (AB3 and AB4) compared to TE; however, it was found that RF muscle activity in the equipment was significantly higher compared to TE. Thus, it is concluded that traditional abdominal exercise prioritizes the recruitment of abdominal muscles while minimizing hip flexor muscle activity, a factor of great importance in its choice when compared to the Ab Max Genis® equipment, especially for individuals with weak abdominal musculature and lumbar spine problems.